A Comparative Study of Work Culture, Job Performance, and Subjective Well-being of Private and Public Sector Banks. Issue 2 (December 2016) - Sharma, Devina; Joshi, Uma
The research article compares the work culture (openness, confrontation, trust, authenticity, proactivity, autonomy, collaboration, and experimentation [OCTAPACE]), job performance, and subjective well-being (SWB) as perceived by the employees of private and public sector banks. This research was based on 400 officers and middle-level managers of four private sector banks (Axis Bank, HDFC Bank, ICICI Bank, and ING Vysya Bank) and four public sector banks (Bank of India, Bank of Baroda, Punjab National Bank, and State Bank of India) from different cities of Uttar Pradesh (Agra, Kanpur, and Lucknow) and Delhi. Using Student's t -test ( t ), analysis of variance (ANOVA; F -ratio), Pearson product–moment correlation ( r ), and multiple regression ( R ), it was established that the employees of public sector banks scored significantly higher in perceived work culture, job performance, and SWB (and in their respective components) than the employees of private sector banks. A high positive inter-correlation was observed amongst them. Work culture positively influenced job performance and SWB. The biggest determinant of SWB was job performance, and work culture has the least role in it.